Micropropagation of clonal lines of thorny artichoke (Cynara scolymus L.) - Catacora, E. (2019)
The aim of the study was to evaluate the in vitro propagation ability of 10 clonal lines of thorny globe artichoke (Cynara scolymus L.). The study methodology comprised five stages of evaluation. The stages evaluated were initiation, multiplication, rooting, acclimatization, and transplant to the field. The study began with the initiation of dissected shoot tips of 10 clonal lines in test tubes containing the Murashige and Skoog (MS) medium. Best results were obtained when explants were cultured on an induction medium containing MS + naphthalene acetic acid (NAA) 1.0 mg l−1 + benzyl aminopurine (BA) 1.0 mg l−1, highlighting clonal lines L-250, L-132, and L-62. Because of high rates of vitrification and phenolization in the initial stage, clonal lines L-24, L-127, and L-142 were discarded from the study. Therefore, only seven clonal lines were included for evaluation in the multiplication stage. Once the microplants were obtained under laboratory condition in the culture medium, they were immediately transferred to a proliferation medium containing MS + BA 1.0 mg l−1. Only in three clonal lines (L-132, L-200, and L-250), a high multiplication rate (3.5 shoots/explant) was achieved with axillary bud formation. Of the seven clonal lines evaluated, clonal line L-250 achieved the highest rates in the variables shoot height (3.38 cm), number of leaves (13.4), and number of shoots/explant (4.4). In the rooting stage, clonal line L-250 obtained a significant improvement by transferring plantlets to direct acclimatization after 20 days of in vitro root induction in a medium containing MS + NAA 1.0 mg l−1. Similarly, in the acclimatization stage, the clonal line L-250 showed a significant result. Then, in the transplantation stage, the plants were transplanted to the field with 100% rooting; 30 days after the transplantation, the clonal line L-250 obtained 100% survival in the field than the control treatments (offspring from two locations were used – Mito and Alayo). As the rooting period is reduced by approximately 20 days by inducing direct root formation under greenhouse conditions, the micropropagation technique is optimized with the protocol used in this study.